One‐year survival after out‐of‐ hospital cardiac arrest: Sex‐based survival analysis in a Canadian population - Awad, Emad; Fordyce, Christopher B.; Grunau, Brian; Christenson, Jim; Helmer, Jennie; Humphries, Karin (Journal of the American College of Emergency Physicians Open, 2023)
We investigated sex differences in 1‐year survival in a cohort of patients who survived out‐of‐hospital cardiac arrest (OHCA) to hospital discharge. We hypothesized that female sex is associated with higher 1‐year posthospital discharge survival. A retrospective analysis of linked data (2011–2017) from clinical databases in British Columbia (BC) was conducted. We used Kaplan–Meier curves, stratified by sex, to display survival up to 1‐year, and the log‐rank test to test for significant sex differences. This was followed by multivariable Cox proportional hazards analysis to investigate the association between sex and 1‐year mortality. The multivariable analysis adjusted for variables known to be associated with survival, including variables related to OHCA characteristics, comorbidities, medical diagnoses, and in‐hospital interventions. We included 1278 hospital‐discharge survivors; 284 (22.2%) were female. Females had a lower proportion of OHCA occurring in public locations (25.7% vs. 44.0%, P < 0.001), a lower proportion with a shockable rhythm (57.7% vs. 77.4%, P < 0.001), and fewer hospital‐based acute coronary diagnoses and interventions. One‐year survival for females and males was 90.5% and 92.4%, respectively (log‐rank P = 0.31). Unadjusted (hazard ratio [HR] males vs. females 0.80, 95% confidence interval [CI] 0.51–1.24, P = 0.31) and adjusted (HR males vs. females 1.14, 95% CI 0.72–1.81, P = 0.57) models did not detect differences in 1‐year survival by sex. Females have relatively unfavorable prehospital characteristics in OHCA and fewer hospital‐based acute coronary diagnoses and interventions. However, among survivors to hospital discharge, we found no significant difference between males and females in 1‐year survival, even after adjustment.